Characteristics of Children With Inflammatory Bowel Disease and Coexisting Celiac Disease Seropositivity. Issue 6 (19th September 2022) - Cheung, Telly; de Zoeten, Edwin F.; Hoffenberg, Edward J.; Liu, Edwin; Pan, Zhaoxing; Walker, Thomas; Stahl, Marisa
Abstract : Objectives: Celiac disease (CeD) autoimmunity and coexisting inflammatory bowel disease (IBD) present a diagnostic dilemma. Our aims were to describe the phenotype of children with IBD and CeD seropositivity and evaluate provider confidence for diagnosing CeD in this population. Methods: We performed a single-center retrospective cohort study of subjects ≤18 years old with IBD and CeD seropositivity between 2006 and 2020. Subjects were considered to have IBD-CeD if they met CeD diagnosis by serology and histology per North American Society For Pediatric Gastroenterology, Hepatology and Nutrition guidelines and if providers suspected CeD as evaluated by a survey. The IBD-only cohort included seropositive participants that did not meet criteria for CeD. Demographic, histologic, gross endoscopic, and laboratory features were compared using Fisher exact test. Results: Of 475 children with IBD, 8 had concomitant CeD, 5 had tissue transglutaminase (tTG) immunoglobulin A (IgA) > 10x upper limit of normal (ULN, P = 0.006), and 8 had villous atrophy (VA, P = 0.003) when compared with 17 seropositive participants with IBD-only. No children with IBD-CeD had esophageal eosinophilia, duodenal cryptitis, duodenal ulceration, or fecal calprotectin >250 µg/g. Factors that contributed to provider uncertainty for diagnosing CeD in IBD included the absence of VA and intraepithelial lymphocytes, the presence of neutrophilic and eosinophilic duodenitis, diffuse ulceration, elevated inflammatory markers, and immunosuppression therapy. Conclusions: Diagnosing CeD in children with IBD continues to be challenging. Although high titers of tTG IgA and VA increased provider confidence for diagnosing CeD in IBD, development of evidence-based guidelines are needed. They should better assess the importance of features atypical of concomitant CeD that contribute to uncertainty.